Phronesis Dimension (Al-Syu’ur Al-’Fadhillah) As A New Manhaj Of Contemporary Fiqh: Case Study of Central MUI Fatwa No. 14 of 2021 and East Java MUI Fatwa No. 1 of 2021 on the Law of AstraZeneca’s COVID-19 Vaccine Products - Muzzammil, Shofiyullah (JAWAB: Journal of Asian World and Islamic Behavior Journal of Asian World and Islamic Behavior, 2023)
Before the vaccination movement, MUI evaluated the fiqh of various vaccinations in Indonesia, including the contentious AstraZeneca vaccine. The AstraZeneca vaccination was deemed halal by the Indonesian Ulema Council (MUI) of East Java in its Fatwa Number 1 of 2021. Using the justification of istihalah (transforming impure items into something else), East Java MUI pronounced the AstraZeneca vaccination halal. By citing the Shafi’iyah madhhab, which upholds the principle of caution (ikhtiyath), and avoiding controversy, the Central MUI ruled the AstraZeneca vaccine to be haram-mubah because it did not accept istihalah in the process of istinbath pork products contaminated with pork elements and their derivatives (khuruj minal khilaf). The goal of maslahah wal fadhillah, or maximizing profit by prudent and effective preventative measures, is the philosophy of fiqh.